2017
DOI: 10.1002/1873-3468.12859
|View full text |Cite
|
Sign up to set email alerts
|

Enolase binds to RnpA in competition with PNPase in Staphylococcus aureus

Abstract: The RNA degradosome of the pathogen Staphylococcus aureus regulates the metabolism of RNA, the expression of virulence factors, and the formation of biofilms. It is composed of the RNases J1/J2, RNase Y, CshA, PNPase, Enolase, Pfk, and a newly identified component, RnpA. However, the function and new partners of RnpA in RNA degradosome remain unknown. Here, we identified PNPase and Enolase as two novel partners for RnpA. Further studies revealed that Enolase interacts with RnpA in competition with PNPase. Enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…To better understand the binding modes of the prepared naphthoquinone analogues (5 b, 5 j, and 5 q), a docking model was created using the crystal structure of the S. aureus PNPase catalytic domain (PDB ID: 5XEX). [43] Prior to molecular docking, the crystal structure of S. aureus receptor was prepared using the protein preparation wizard in Schrödinger Maestro (version 8.5, Schrödinger, LLC, New York, 2010). The crystal structure was downloaded from the protein data bank (PDB), and the chemical structures of the compounds were sketched using ChemDraw professional 15.1.…”
Section: In Silico Molecular Docking Studymentioning
confidence: 99%
“…To better understand the binding modes of the prepared naphthoquinone analogues (5 b, 5 j, and 5 q), a docking model was created using the crystal structure of the S. aureus PNPase catalytic domain (PDB ID: 5XEX). [43] Prior to molecular docking, the crystal structure of S. aureus receptor was prepared using the protein preparation wizard in Schrödinger Maestro (version 8.5, Schrödinger, LLC, New York, 2010). The crystal structure was downloaded from the protein data bank (PDB), and the chemical structures of the compounds were sketched using ChemDraw professional 15.1.…”
Section: In Silico Molecular Docking Studymentioning
confidence: 99%
“…In this study, the RnpA knockdown system was developed using the synthetic regulatory small RNA system [ 20 ] since the RnpA protein, which is essential for cell viability, was reported to degrade mRNAs in vitro. [ 71 ] When introduced to a recombinant E. coli strain expressing the fluorescent mCherry protein, the RnpA knockdown system significantly increased the fluorescence intensity as well as the mCherry protein level while overexpression of rnpA decreased both the fluorescence intensity and the mCherry protein level. The general applicability of the RnpA knockdown system was also demonstrated by examining its positive effects on protein overproduction in 14 different E. coli strains.…”
Section: Discussionmentioning
confidence: 99%
“…aureus, and others have also targeted the thioredoxin system . Polynucleotide phosphorylase (PNPase) is a bifunctional exoribonuclease responsible for mRNA turnover by dismantling the RNA chain starting at the 3′ end and working toward the 5′ end and synthesizing long, highly heteropolymeric tails in vivo . It acts as quality control for rRNA precursors in several bacteria, including S.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Polynucleotide phosphorylase (PNPase) is a bifunctional exoribonuclease responsible for mRNA turnover by dismantling the RNA chain starting at the 3′ end and working toward the 5′ end and synthesizing long, highly heteropolymeric tails in vivo . 24 It acts as quality control for rRNA precursors in several bacteria, including S. aureus . We retrieved these proteins from the AlphaFold database for S. aureus (strain MRSA252) to perform molecular docking studies for our compounds since they have been reported to play a significant role in the survival of our target microorganisms.…”
Section: Introductionmentioning
confidence: 99%